Analisis Data Kemampuan Menghafal Alquran Dengan Menggunakan Model Regresi Untuk Data Berdistribusi Normal Terpotong Atas Bawah (Jurnal EurekaMatika, 2020)
The objective of this research is to analyze data on Quranic memorization ability, obtained from tahfizh examination results using a test instrument, and analyzed using a truncated regression model. Given the restrictions on the dependent variable's values and that the independent variables are only observed when the dependent variable is observed, the analysis utilizes a doubly truncated normal distribution.  In the regression model for this data, the values of the dependent variable are q
Keywords: Kemampuan menghafal Alquran; Model regresi data berdistribusi normal terpotong atas bawah